Answered

At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

simplify the expression -6 - 7 (c+10)

Sagot :

Answer:

[tex]-6-7\left(c+10\right)=-7c-76[/tex]

Step-by-step explanation:

Given the expression

[tex]-6\:-\:7\:\left(c+10\right)[/tex]

simplifying the expression

[tex]-6-7\left(c+10\right)[/tex]

Expanding -7(c + 10) = -7c - 70

[tex]-6\:-\:7\:\left(c+10\right)=-6-7c-70[/tex]

subtract the numbers: -6 - 70 = -76

                           [tex]=-7c-76[/tex]

Therefore, we conclude that:

[tex]-6-7\left(c+10\right)=-7c-76[/tex]